Atrial fibrillation ablation by single ring isolation versus wide antral isolation: Effects on left atrial size and function. (1st March 2016) - Lee, Adam; See, Valerie A.; Lim, Toon Wei; Descallar, Joseph; Chik, William; Ross, David L.; Thomas, Stuart P.; Thomas, Liza
Abstract: Background: Pulmonary vein isolation (PVI) by single ring isolation (SRI) has been demonstrated to reduce recurrence of atrial fibrillation (AF) compared to the standard technique of wide antral isolation (WAI). In this study, we examine the differential effect of these techniques on left atrial size and function. Methods: We examined left atrial (LA) size (LA maximum and LA minimum volumes) and function (LA emptying fraction and LA expansion index) over a period of 6 months following PVI as measured by transthoracic echocardiography in 187 patients that were enrolled in a randomised controlled trial of SRI vs WAI. Results: Compared to pre-ablation, at 6 months post-PVI, there was a small decrease in the LA maximum volume in the WAI group (67.3 vs 62.7 mL, p = 0.02). The LA size did not change significantly over 6 months in the SRI group. Patients who underwent SRI had a small reduction in the LA expansion index at 6 months post-PVI compared to baseline (80.6 vs 66.6%, p = 0.02). LA function did not change significantly over 6 months in the WAI group. However, at 6 months, there was no difference in any measure of LA size or function between the SRI and WAI groups. Conclusions: SRI, whilst previously demonstrated to be more effective than WAI in preventing AF recurrence, is associated with minimal adverse effects on left atrial function at medium term follow-up despite the isolation of a larger region of LA myocardium.